THE INFLUENCE OF AUDIT COMMITTEE, PROFITABILITY AND AUDIT QUALITY ON TIMELINESS OF FINANCIAL REPORTING IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES IN THE PERIOD 2021-2023 - Yudea; BERTOLD Yunus; Hairul Anam; Wiwik Saraswati (Faculty of Economics and Business, Universitas Warmadewa, 2025)
This study aims to examine the influence of the Audit Committee, Profitability and Audit Quality on Timeliness of Financial Reporting. The data used are the annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2023. The type of research used is quantitative research. The sampling technique used a purposive sampling method which resulted in 197 company samples from a population of 95 companies. The data analysis method used is descriptive statistical analysis and multiple linear regression analysis. The results of this study indicate that the Audit Committee has a negative and significant effect on the timeliness of financial reporting. Profitability has a positive and significant effect on the timeliness of financial reporting. Audit Quality has no effect on the timeliness of financial reporting